2023
DOI: 10.3390/tropicalmed8020098
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Off-Host Stages of Tunga penetrans in the Soil within the Home Range of Nine Infected Dogs in An Endemic Tourist Area in Brazil

Abstract: Tungiasis is a neglected disease caused by the sand flea Tunga penetrans, and dogs are considered the main reservoirs in Brazil. This study aimed to identify the role of dogs as tungiasis dispersers and to investigate the presence of T. penetrans in the soil of an endemic tourist area. Nine dogs infected by T. penetrans were included in this study and received GPS collars to analyze their movement through the village. Duplicate sand samples were collected in different areas of the community. Those areas were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, the neglect of owners, either by not identifying the lesions or not removing the parasitee, makes the disease difficult to control. Thus, there is a need for broad educational awareness actions among dog owners, stressing the effectve canine therapeutic and prophylactic measures to achieve the One Health concept ( Harvey et al, 2021 ; Jesus, 2023 ; Santos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the neglect of owners, either by not identifying the lesions or not removing the parasitee, makes the disease difficult to control. Thus, there is a need for broad educational awareness actions among dog owners, stressing the effectve canine therapeutic and prophylactic measures to achieve the One Health concept ( Harvey et al, 2021 ; Jesus, 2023 ; Santos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tungiasis is a dermatological parasitic disease caused by the sand flea Tunga spp. (Siphonaptera, Tungidae) that affects domestic and wild animals ( Jesus, 2023 ; Santos et al, 2022 ) and humans ( Pampiglione et al, 2009 ). The dermatopathy is related to the penetration, maturation and thickening of the flea body in the host's skin ( Harvey et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The streets are unpaved and consist of sandy and clay soil, and some buildings are unfinished without concrete floors [ 8 , 25 ]. Moreover, the study area had previously shown a high year-round prevalence of tungiasis in dogs [ 8 , 16 , 23 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The participation of dogs in the dynamics of the disease is evident in endemic locations, as these animals have a wide circulation area and cover large perimeters, spreading flea eggs in the environment and facilitating the establishment of the parasite's biological cycle [ 15 , 16 ]. Environmental contamination caused by infested animals can be prevented by controlling the fleas in the host.…”
Section: Introductionmentioning
confidence: 99%
“…Data were retrieved from the MapBiomas v.5.0 platform (as raster image of 30 m resolution, 4.0 collection), which makes the catalog of images of Brazil with different categories of LCSU publicly available (MAPBIOMAS 2022). QGIS v.3.8 software was used to create a 3 km radius buffer area around each animal's origin (28.3 km 2 ), which was assumed to be their home range (Jesus et al 2023). The proportion of each LCSU type of in the raster image within the buffer area of each animal was calculated.…”
Section: Association With Land Cover Typesmentioning
confidence: 99%